A new species of the genus Aristochroa Tschitscherine, 1898 (Coleoptera, Carabidae, Pterostichini) from Yunnan, China - Azadbakhsh, Saeed (Zootaxa, 2017)
A new species of the genus Aristochroa Tschitscherine, 1898 (Coleoptera: Carabidae), namely Aristochroa nozari sp. n., is described and illustrated from Yunnan Province, China. The new species is compared with closely related species.